Cultural, chemical and genetic management of Moniliophthora roreri in Chiapas, Mexico - Castillo-Martínez, Antonio; Ogaz, Alfredo; López-Hernández, Javier; Mora-Aguilera, José Antonio; García López, Elvis (Ecosistemas y Recursos Agropecuarios, 2024)
Frosty pod rot (Moniliophthora roreri) disease damages cocoa fruits at any stage of development, causing abandonment of the crop, demolition and change of land use. The objective of this study was to optimize the management of frosty pod rot of cocoa based on chemical, cultural and varietal use control practices. In Mapastepec, Chiapas, five plots, each with 24 cocoa trees, were evaluated in a completely randomized design with factorial arrangement. Productivity and disease incidence variables were evaluated on CATIE-R1, CATIE-R4 and CATIE-R6 varieties, each with five management types and eight repetition. The interaction between genotype, cultural and phytosanitary management with alternate spraying of azoxystrobin with flutriafol and fertilization increased the number of cocoa pods by 48.5% and reduced the incidence of Moniliophthora roreri by 30.3%.
Keywords: Cultural management; phytosanitary management; azoxystrobin; frosty pod rot